Synchrotron powder diffraction studies of metal-organic frameworks - Morris, Christopher (2017)
This thesis describes a variety of high resolution synchrotron powder diffraction studies of guest-loaded metal-organic frameworks (MOFs). These studies have been used to provide insight into the binding mechanisms of the guest molecules. Chapter 1 contains an introduction to MOFs, highlighting some potential applications that were investigated in this work. A description of the powder diffraction analysis techniques is also included. Chapter 2 describes the design and implementation of a remote control gas dosing system for use on the powder diffraction beamline (I11) at Diamond Light Source. To assess the precision of this system, and to gain an insight into the high CO2/N2 selectivity of the V(III) MOF, MFM-300(V), an in situ powder diffraction experiment was performed, firstly using pure CO2 and then with an equimolar mixture of CO2/N2. Two CO2 sites were found in all cases, with CO2-A forming a dipole-dipole interaction with the framework’s hydroxyl group, and CO2-B interacting with CO2-A via further dipole-dipole interaction. In the presence of N2, particularly at low loadings, the positions of the CO2 molecules vary quite significantly due to the presence of disordered N2 within the pore. Further to this investigation, the long term SO2 adsorption stability of the Al(III) MOF, MFM-300(Al), was studied by powder diffraction. The SO2-loaded MOF was found to remain stable over a period of 37 weeks. In Chapter 3, an investigation into the C8 hydrocarbon vapour adsorption and liquid phase separation properties of MFM-300(M) (M=Al, V, In) is described, with supporting structural information obtained from high resolution powder diffraction. In the vapour phase, MFM-300(Al) was the only MOF of the three studied to show any discrimination between the 4 isomers, whereas in the liquid phase, it showed no significant separation. Conversely, MFM-300(In) showed the highest degree of separation of m-xylene from ethylbenzene and o-, and p-xylene, however this was accompanied by poor separation of ethylbenzene and o-xylene. MFM-300(V) showed a lesser degree of separation of m-xylene from ethylbenzene and o-, and pxylene, but with a much better separation of ethylbenzene and o-xylene. The structural studies revealed π-π stacking interactions between the C8 hydrocarbons and the phenyl ring of the framework, and in the case of MFM-300(In)(p-xylene), tetragonal I4122 → orthorhombic I212121 phase change was observed. To further investigate the apparent flexible nature of MFM-300(In), high pressure powder diffraction was used, and a similar phase change was observed at 0.584 GPa. Chapter 4 describes the synthesis and characterisation of a Zr(IV) MOF, MFM-450. The CO2 and N2 adsorption properties of this MOF were investigated, and it was found to adsorb 2.32 mmol/g CO2 at 273 K, followed by 1.97 mmol/g CO2 at 283 K, and 1.48 mmol/g CO2 at 298 K. The N2 adsorption at these temperatures was negligible, resulting in high selectivities. To investigate the nature of CO2 binding in MFM-450, in situ powder diffraction was used. Two CO2 adsorption sites were found. The site in cage A was found to interact with the phenyl ring of the framework via π-π interactions, and the site in cage B interacts with the carboxylate group of the phenyl ring via a dipole-dipole interaction.